Miracles happen : the life and timeless principles of the founder of Mary Kay Inc. - Ash, Mary Kay; Ash, Mary Kay. (New York : Quill, 2003)
Cosmetics maven Mary Kay Ash tells the story of her life, discussing her childhood in rural Texas, her struggles as a single mother, her success in direct sales, and her founding of the Mary Kay Cosmetics company in her post-retirement years
Originally published: Mary Kay. 1st ed. New York : Harper & Row, c1981
Keywords: Ash, Mary Kay; Mary Kay Cosmetics -- History; Cosmetics industry -- United States -- History; Industrialists -- United States -- Biography; Businesswomen -- United States -- Biography